2015
DOI: 10.1016/j.ijimpeng.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of projectile nose shape on ballistic resistance of interstitial-free steel sheets

Abstract: In this paper an experimental and numerical work is reported concerning the process of perforation of thin steel plates using different projectile nose shapes. The main goal is to analyze how the projectile shape may change the ballistic properties of materials. A wide range of impact velocities from 35 to 180 m/s has been covered during the tests. All the projectiles were 13mm in diameter and the targets were 1mm thick, as such the projectile can be regarded as rigid and the target sheets were of interstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Beyond 175 m/s, mass inertial effects are important, i.e., no dependence on the projectile geometry is found in the residual impact velocity. This behavior has been observed in other research [ 5 , 29 ].…”
Section: Numerical and Experimental Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Beyond 175 m/s, mass inertial effects are important, i.e., no dependence on the projectile geometry is found in the residual impact velocity. This behavior has been observed in other research [ 5 , 29 ].…”
Section: Numerical and Experimental Resultssupporting
confidence: 89%
“…al. [ 9 ] and Kepenyigba et al [ 5 ], triaxiality depends on the projectile nose shape. Blunt projectiles produces a tensional state of shearing (triaxiality = 0), conical projectile produces a tensional state by piercing with a triaxiality of 1/3, and hemispherical projectiles produces a mixed tensional state (triaxiality = 2/3).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that residual velocity after perforation was similar for a conical-and a hemispherical-shaped object, while the lowest value was found for a cylindrical projectile. Visible correlation between the projectile shape and the energy absorption capacity of a target was presented in the paper by Kpenyigba et al [34]. It was found that the hemispherical-nosed impactor was the least efficient, followed by conical and two double nosed.…”
Section: Introductionmentioning
confidence: 95%
“…The value of the impact velocity at the point where the fitted curve intersects with the horizontal axis defines the ballistic limit which is shown by v 50 . Equation (3) is frequently used for determining the ballistic limits of materials [17,18]. The ballistic limit may be affected by the geometry of projectile and the target [19,20] and also by heat treatment of the material [21].…”
Section: Introductionmentioning
confidence: 99%